2020
DOI: 10.3389/fpsyt.2020.00419
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Weight-Loss Surgery in People With Serious Mental Illness: A Qualitative Study

Abstract: Background: Bariatric surgery is seldom accessed by people with serious mental illness, despite high rates of obesity in this population. It is sometimes assumed that patients with complex psychiatric histories will have poor post-surgical weight loss or exacerbation of psychiatric symptoms, although this is unsubstantiated.Objectives: A qualitative descriptive study to explore personal experiences and the impact of bariatric surgery on physical and mental well-being and life-quality in individuals with seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…A qualitative study found that patients with severe psychiatric issues benefited from BMS, which improved their quality of life and physical and mental health. The study tested a broad spectrum of PI diagnoses, including severe depressive disorder, bipolar disorder, and schizoaffective disorder, and found that patients self-requested extra care and support for obesity treatment and aftercare [ 11 ]. Therefore, allowing extra time, attention, and listening to the patient can help improve mental health outcomes in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study found that patients with severe psychiatric issues benefited from BMS, which improved their quality of life and physical and mental health. The study tested a broad spectrum of PI diagnoses, including severe depressive disorder, bipolar disorder, and schizoaffective disorder, and found that patients self-requested extra care and support for obesity treatment and aftercare [ 11 ]. Therefore, allowing extra time, attention, and listening to the patient can help improve mental health outcomes in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The focus has been mainly on antipsychotic drug-induced weight gain and schizophrenia [ 9 , 10 ]. Another study found that BMS effectively reduced psychiatric patients’ body weight and improved their quality of life, especially in those with severe depressive, bipolar, and schizoaffective disorders [ 11 ]. In addition, patients with bipolar disorders who underwent Roux-en-Y gastric bypass (RYGB) had successful weight loss outcomes at 12 months, which did not significantly differ from those of patients without PIs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight gain is a well-recognised and particular troubling side-effect of many antipsychotic medications. 17 Given the implications of obesity for subjective well-being, medication adherence and therapeutic outcomes in the context of treatment for psychosis, and associated diabetes and cardiovascular risk and likelihood of premature mortality, [44][45][46] improving interventions in this area needs to remain a focus for researchers. To date, studies of current weight management programmes for people with psychosis have produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Aotearoa New Zealand (NZ) reported that 23% of people with MHSUC experienced discrimination from health services ( 20 ). Examples of discrimination include acting on stereotypes and prejudice, such as clinicians avoiding patients with MHSUC due to unwarranted fear of violence or discomfort with mental illness ( 21 ) and patients with MHSUC being denied weight loss surgery due to unsubstantiated assumptions they will have poorer outcomes ( 22 ). Discrimination from clinicians can also deter people from seeking treatment ( 23 ), creating further barriers to appropriate diagnosis and treatment of physical conditions.…”
Section: Introductionmentioning
confidence: 99%